THEORETICAL AND PRACTICAL PROBLEMS IN DESIGNING TESTS FOR FOREIGN LANGUAGE PROGRAMS - Rapi, Leonard; Miconi, Harallamb (European Scientific Journal, ESJ, 2014)
Testing is an important component in foreign language programs. This occurs for a number of reasons. First, foreign language teachers systematically test their students in order to assess their performance and achievements in the learning process. On the basis of their test results, teachers make decisions which affect their students’ further progress. For example, they decide whether their students have acquired the material for which they have been tested or whether action should be taken to help those whose performance results problematic. In more extreme cases, it is test results again that determine whether a student may move on to an upper level or not. Second, tests may have scientific purposes. They may be applied to foreign language classes as part of scientific studies to collect data linked to various aspects of learning-teaching foreign languages. In this context, an issue of great importance is that of the reliability and validity of the administered tests. To what extent can we claim that these tests serve as reliable indicators of the level of acquisition of the subject material by our students? The fact is that when there is practically no training whatsoever in the field of test development, teachers often rely mostly on their own intuition or their previous experience as students or turn to tests that come with the textbooks they use. In view of the above, this article will discuss some problems which have to do with test design and development in language programs as well as their possible implications for our teachers.